2012
DOI: 10.5535/arm.2012.36.4.521
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Effects of Newly Developed Balance Control Trainer for Mobility and Balance in Chronic Stroke Patients: A Randomized Controlled Trial

Abstract: ObjectiveTo investigate the feasibility and effects of balance training with a newly developed Balance Control Trainer (BCT) that applied the concept of vertical movement for the improvements of mobility and balance in chronic stroke patients.MethodForty chronic stroke patients were randomly assigned to an experimental or a control group. The experimental group (n=20) underwent training with a BCT for 20 minutes a day, 5 days a week for 4 weeks, in addition to concurrent conventional physical therapy. The cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 25 publications
0
13
0
6
Order By: Relevance
“…These results support our first hypothesis that "treadmill gait training and deep-water gait training will lead to similar functional adaptations". In fact, other studies have shown that gait training in the rehabilitation pool or treadmill improves BBS after training 25,26 . Our first hypothesis was associated to the aerobic training effect and the importance of improving overall fitness state as a tool to improve function.…”
Section: Discussionmentioning
confidence: 99%
“…These results support our first hypothesis that "treadmill gait training and deep-water gait training will lead to similar functional adaptations". In fact, other studies have shown that gait training in the rehabilitation pool or treadmill improves BBS after training 25,26 . Our first hypothesis was associated to the aerobic training effect and the importance of improving overall fitness state as a tool to improve function.…”
Section: Discussionmentioning
confidence: 99%
“…With its unique movement training system, the BCT achieves greater improvements in balance and mobility in stroke patients [ 21 ]. Although other computerized dynamic posturography measures only the horizontal body weight distribution, the BalPro training system includes not only horizontal movement, but also vertical movement.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study on balance control training using the balance control trainer (BCT) shows a remarkable training effect on improving balance disability [ 21 ]. Furthermore, the training effect was measured using several outcome measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, our research team developed a new lower limb balance control trainer (BalPro; Man&Tel, Gumi, Korea) that is capable of providing vertical movement as well as horizontal movement and task-oriented lower limb exercise. Lee et al [ 10 ] showed that the balance control trainer, the previous version of the BalPro, was beneficial when used for chronic stroke patients who were somewhat able to stand and walk but had balance problems. They reported that balance and gait ability were improved after using the balance control trainer.…”
Section: Introductionmentioning
confidence: 99%